Tryptophan residue of plasmid-encoded Pgp3 is important for Chlamydia muridarum to induce hydrosalpinx in mice - Huang, Yumeng; Wu, Haoqing; Sun, Yina; Liu, Yuanjun (Frontiers in Microbiology, 2023)
The crucial role of plasmid-encoded protein Pgp3 on Chlamydia pathogenesis has been demonstrated in various animal models. Previous studies have revealed that Pgp3-decifient C. muridarum mutant fails to induce hydrosalpinx after vaginal inoculation in mice. Structural analysis of C. trachomatis Pgp3 trimer has indicated that Trp234 may play a critical role in trimeric crystal packing interactions and Tyr197 involved at predominant cation-binding sites. In this study, we constructed C. muridarum transformants harboring Pgp3 Trp234 or Tyr197 point mutation (Pgp3W234A and Pgp3Y197A). C3H/HeJ mice infected with Pgp3W234A mutant failed to induce severe hydrosalpinx in oviduct tissue, which largely phenocopied the full length Pgp3-deficient C. muridarum. The Pgp3Y197A variant induced an intermediate severity of pathology. The attenuated pathogenicity caused by the Pgp3W234A mutant may be due to its decreased survival in the lower genital tracts of mice, reduced ascension to the oviduct, and milder induction of inflammatory cell infiltration of oviduct tissue. Thus, our results point to an important amino acid residue involved in Pgp3 virulence, providing a potential therapeutic target for chlamydial infection.